2013
DOI: 10.3354/esr00515
|View full text |Cite
|
Sign up to set email alerts
|

Seismic operations have variable effects on dive-cycle behavior of bowhead whales in the Beaufort Sea

Abstract: The surfacing, respiration and diving (SRD) behavior of bowhead whales Balaena mysticetus changes upon exposure to seismic operations. However, it is unknown whether these changes differ by season, reproductive status (calves, mothers, and non-calves), and whale activity (traveling, foraging, or socializing). Such SRD behavioral responses to seismic operations might influence the detectability of whales during aerial surveys. We addressed these questions by applying non-parametric univariate tests and linear m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 46 publications
2
27
0
Order By: Relevance
“…A number of behavioural studies of baleen whale responses to potential anthropogenic disturbance have found that response is highly dependent on the context of the exposure, e.g. factors such as season or an animal's behavioural state and reproductive status (Beale & Monaghan 2004, Beale 2007, Nowacek et al 2007, Southall et al 2007, Ellison et al 2012, Dunlop et al 2013, Robertson et al 2013. Therefore, both 'natural' (e.g.…”
mentioning
confidence: 99%
“…A number of behavioural studies of baleen whale responses to potential anthropogenic disturbance have found that response is highly dependent on the context of the exposure, e.g. factors such as season or an animal's behavioural state and reproductive status (Beale & Monaghan 2004, Beale 2007, Nowacek et al 2007, Southall et al 2007, Ellison et al 2012, Dunlop et al 2013, Robertson et al 2013. Therefore, both 'natural' (e.g.…”
mentioning
confidence: 99%
“…Localized and short-term behavioral responses such as movement toward or away from the sound source or a change in vocalization rates have been reported for some cetaceans during seismic surveys (Richardson et al, 1995;Gordon et al, 1998;Nowacek et al, 2007;Southall et al, 2007;Barry, Cucknell, & Clark, 2012;Castellote, Clark, & Lammers, 2012;Blackwell et al, 2013Blackwell et al, , 2015Thompson et al, 2013;Robertson et al, 2013;Cerchio, Strindberg, Collins, Bennett, & Rosenbaum, 2014;Pirotta, Brookes, Graham, & Thompson, 2014;Wole & Myade, 2014;Dunlop et al, 2015Dunlop et al, , 2016Muir et al, 2015Muir et al, , 2016Finneran et al, 2015;Gailey et al, 2016). However, the long-term consequences of airgun sounds on marine mammals are mostly unknown, and the effectiveness of mitigation measures are largely uncertain (Cato et al, 2013;Nowacek et al, 2013;Wright & Consentino, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…For example, targeted studies to examine pathology of stranded animals in areas with/without seismic activities could lend insights into physiological impacts of animals exposed to sound. All of these types of studies could be conducted in areas of recurring surveys, such as around Sakhalin Island, Russia (Bröker et al 2015, Muir et al 2015, West Africa (DeRuiter & Doukara 2012), and the Beaufort Sea (Richardson & Miller 2013, Robertson et al 2013, to name just a few places. Ideally, this type of information would be collected at an individual-and population-level setting to determine demographic consequences from surveys.…”
Section: Examine the Extent And Duration Of Avoidance Behavior And Hmentioning
confidence: 99%